El ceremonial y protocolo en la Unidad Educativa Particular Santa Mariana de Jesús y su incidencia en la imagen institucional, período enero a julio de 2014. - Carpio Costa, Maritts Angelita (2016)
This research is titled “The Ceremonial and Protocol Aspects of the Special Education Unit Santa Mariana of Jesus and its Impact on Corporate Image for the Time Period of January to July 2014.” The purpose of this research was to obtain information on the conduct of institutional events and to evaluate how it influences the image that the public has of the education unit. The investigation began with obtaining information on the entity and by studying the variables of Ceremonial and Protocol and Institutional Image. Questionnaires were used to interview parents, staff, faculty, and students regarding the organizational procedures and events and how these things affect the image that the public has of the educational unit. The research presents the results in statistical tables and graphs and provides an analysis and interpretationof the information relative to the theoretical framework. Additionally, the research presents conclusions and recommendations based on the data findings